Proceedings of the 2019 Conference on Empirical Methods in Natural Language Processing and the 9th International Joint Conferen 2019
DOI: 10.18653/v1/d19-1009
|View full text |Cite
|
Sign up to set email alerts
|

Game Theory Meets Embeddings: a Unified Framework for Word Sense Disambiguation

Abstract: Game-theoretic models, thanks to their intrinsic ability to exploit contextual information, have shown to be particularly suited for the Word Sense Disambiguation task. They represent ambiguous words as the players of a non-cooperative game and their senses as the strategies that the players can select in order to play the games. The interaction among the players is modeled with a weighted graph and the payoff as an embedding similarity function, which the players try to maximize. The impact of the word and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Word Sense Disambiguation (WSD) is a core task in lexical semantics and has mainly been tackled by two kinds of approach: knowledge-based and supervised ones. Knowledge-based methods build upon lexical knowledge bases, such as WordNet (Miller et al, 1990) and BabelNet (Navigli and Ponzetto, 2012), and employ algorithms on graphs to address the word ambiguity in texts (Moro et al, 2014;Agirre et al, 2014;Tripodi and Navigli, 2019;. These approaches do not rely on semantically-tagged training data and are hence able to scale over all the languages supported by their underlying knowledge base.…”
Section: Related Workmentioning
confidence: 99%
“…Word Sense Disambiguation (WSD) is a core task in lexical semantics and has mainly been tackled by two kinds of approach: knowledge-based and supervised ones. Knowledge-based methods build upon lexical knowledge bases, such as WordNet (Miller et al, 1990) and BabelNet (Navigli and Ponzetto, 2012), and employ algorithms on graphs to address the word ambiguity in texts (Moro et al, 2014;Agirre et al, 2014;Tripodi and Navigli, 2019;. These approaches do not rely on semantically-tagged training data and are hence able to scale over all the languages supported by their underlying knowledge base.…”
Section: Related Workmentioning
confidence: 99%
“…Word Sense Disambiguation (WSD) is one of the challenging problems in natural language processing. Typical WSD models (Lesk, 1986;Zhong and Ng, 2010;Yuan et al, 2016;Raganato et al, 2017;Le et al, 2018;Tripodi and Navigli, 2019) are trained for a general domain. Recent works (Li and Jurafsky, 2015;Mekala et al, 2016;Gupta et al, 2019) also showed that machine-interpretable representations of words considering its senses, improve document classification.…”
Section: Word Sense Disambiguationmentioning
confidence: 99%
“…Word Sense Disambiguation (WSD) -the task of assigning the correct meaning to a target word in a context -is considered to be a fundamental step towards natural language understanding (Navigli, 2018). As with many other tasks, WSD has benefited greatly from the recent advances in other fields, such as language modelling (Scarlini et al, 2020b), game theory (Tripodi and Navigli, 2019), structured knowledge integration , definition modelling and label propagation (Barba et al, 2020;, inter alia. Our experiments show that Conception can be used to create state-of-the-art sense embeddings, demonstrating empirically that our approach provides high-quality knowledge that is still not captured by recent language models.…”
Section: Word Sense Disambiguationmentioning
confidence: 99%